Direitos e garantias fundamentais e as relações privadas - Coelho, Luiz Eduardo de Toledo (2010)
The goal of the essay consists in analysing the subject of the aplicability of the fundamental rights and guarantees of the Brazilian Constitution to the private relationships. Other words, to accept the incidence of such fundamental rights in juridic relationships where the State is not present. Doutrine and Jurisprudence were the topics of analysis. At the end, I tried to show that the established relationship between the private owned needs the fundamental rights as much as the public right relationships